Smart Loads for Voltage Control in Distribution Networks - Akhtar,Z; Chaudhuri,B; Hui,S (IEEE Transactions on Smart Grid, 2015)
This paper shows that the smart loads (SLs) couldbe effective in mitigating voltage problems caused by photovoltaic(PV) generation and electric vehicle (EV) chargingin low-voltage (LV) distribution networks. Limitations of thepreviously reported SL configuration with only series reactivecompensator (SLQ) (one converter) is highlighted in this paper.To overcome these limitations, an additional shunt converter isused in back-to-back (B2B) configuration to support the activepower exchanged by the series converter, which increases the flexibilityof the SL without requiring any energy storage. Simulationresults on a typical U.K. LV distribution network are presented tocompare the effectiveness of an SL with B2B converters (SLBCs)against an SLQ in tackling under- and over-voltage problemscaused by EV or PV. It is shown that SLBCs can regulate themain voltage more effectively than SLQs especially under overvoltagecondition. Although two converters are required for eachSLBC, it is shown that the apparent power capacity of eachconverter is required to be significantly less than that of anequivalent SLQ.